PERTUMBUHAN TANAMAN SERAIWANGI (Cymbopogon nardus L) PADA BEBERAPA DOSIS KOMPOS KULIT KOPI - Manurung, Rosliana; Nengsih, Yulistiati; Marpaung, Ridawati; Hartawan, Rudi (Jurnal Media Pertanian, 2021)
The purpose of this study was to determine the effect of giving coffee husk compost on the growth of citronella (Cymbopogon nardus L.) plants. This research was conducted in Kuala Tungkal, Tungkal Ilir District, West Tanjung Jabung Regency, Jambi Province, from December 2020 to March 2021. Analysis of compost nutrients was carried out at the Laboratory of the Jambi Agricultural Technology Research Center and measurements of root wet weight, shoot dry weight and root dry weight were carried out at the Basic Laboratory of Batanghari University Jambi. This research was conducted using a randomized environmental design (CRD) and treatment design for coffee husk compost which consisted of 4 levels of treatment, namely k0 : 3 kg of soil media without treatment (control), k1 : 15 g of coffee husk compost + 2,985 g of soil media, k2 : 22.5 g coffee husk compost + 2.977.5 g soil media, and k3 : 30 g coffee husk compost + 2.970 g soil media. The results of the analysis showed that the application of coffee husk compost had a significant effect on the parameters of root wet weight, shoot dry weight and pH of the growing media but had no significant effect on the parameters of the number of tillers, number of leaves, root dry weight and root crown ratio